Fabrication and characterization of metal-core carbon-shell nanoparticles filling an aeronautical composite matrix. (October 2015) - Zotti, Aldobenedetto; Borriello, Anna; Zuppolini, Simona; Antonucci, Vincenza; Giordano, Michele; Pomogailo, Anatolii D.; Lesnichaya, Valentina A.; Golubeva, Nina D.; Bychkov, Aleksei N.; Dzhardimalieva, Gulzhian I.; Zarrelli, Mauro
Graphical abstract: Highlights: We have prepared composites filled with metal core/polymer shell nanoparticles (NPs). A controlled thermolysis of metal-containing monomers was used to prepare NPs. NPs presence does not negatively affect composite thermal and mechanical properties. A remarkable increase of GIC is observable, higher for low temperature synthesized NPs. Low NPs contents ensure a strong magnetic behaviour of the nanocomposite. Abstract: Metal nanoparticles (NPs) were prepared from acrylamide complex of iron and nickel nitrates by controlled thermolysis at constant temperature in a self-generated atmosphere and used to fabricate epoxy resin nanocomposites. X-ray diffraction performed on the nanoparticles revealed a metal core/polymeric shell structure for the nanoparticles thermolysed at higher temperature as also confirmed by cross analysis of thermo-gravimetrical and vibrating magnetometer data. Optical microscopy was used to investigate the achieved dispersion of the nanoparticles within the uncured resin and transmission electronic microscopy was used to analyse the morphology and the average dimensions of the nanoparticles. Thermal stability of manufactured nanocomposites was studied by thermo-gravimetric analysis in inert and oxidative conditions, reporting that negligible variations are induced by the presence of nanofillers. A complete thermo-mechanical and fracture characterization was carried out to assess the effect of nanoparticles on final nanocomposite system. A slight increase of the modulus is recorded at room temperature whereas a significant variation is induced for higher temperature. The presence of nanoparticles induces a global increase in the fracture energy of nanocomposite associated to different failure mechanisms. Magnetic data indicate that iron particles based nanocomposites display room-temperature ferromagnetic behaviour with saturation magnetization and coercivity depending on the diameter of the metal core.